Urgensi pendidikan Islam dalam membentuk karakter siswa di era revolusi industri 4.0 - Lisnawati, Lisnawati (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Abstract  This article discusses how the teacher's role shifts and how Islamic education shapes the character of students in the midst of the industrial revolution 4.0. The shift in the role of the teacher from previously being teacher centered to becoming a facilitator causes a change in the paradigm of learning orientation to become student centered. The teacher-student interaction process in shaping student character is not as optimal as in the teacher-centered position, it could be because the teachers are no longer flexible or have more space. Therefore, this shift has implications for the creation of a student character crisis. The character crisis of students has recently become a serious problem that is widely discussed and faced by the world of education. It could be because the existence of Islamic religious education which is thick with a traditional approach (teacher oriented) is no longer considered a solution in the new student-oriented paradigm to shape the religious character of students. Even though the research results explain that success in shaping student character through Islamic religious education has so far been created through various extracurricular activities. Because of this, the teacher's ability to insert character values into the learning process, both in intra-curricular and extra-curricular activities is a solution as well as an affirmation that Islamic religious education is a way of building religious student character.